On Dirichlet problems with singular nonlinearity of indefinite sign - Godoy, Tomás Fernando; Kaufmann, Uriel (2022)
Fil: Godoy, Tomás Fernando. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.